PROSES PENGOLAHAN LIMBAH B3 (OLI BEKAS) MENJADI BAHAN BAKAR CAIR DENGAN PERLAKUAN PANAS KONSTAN - Ariasya, Muhammad Ade; ., Azharuddin; Sani, Almadora Anwar (Politeknik Negeri Sriwijaya, Indonesia, 2020)
The use of waste used oil is increasing every year, the resulting waste will also increase. Waste used oil is included in B3 waste which needs special handling. In line with the development of cities and regions, the volume of used oil continues to increase in line with the increase in the number of motorized vehicles and motorized machines. Even in rural areas, you can find small workshops, one of which is used oil. . In other words, the distribution of used oil is very wide from big cities to rural areas throughout Indonesia. The process in this research is changing the waste used oil into liquid fuel with the constant heat treatment. It is aimed to know the best result in the temperature of 250°C, 300°C and 350°C with pyrolysis process. The increase of temperature has a big effect toward the result of the exchanging process. The best result is at the temperature of 350°C which the volume got from the tap A is 1 liter and from the tap B is 0.2 liter. Than the tap sample A was tested against the exiting fuel standards. Based on the result of the specification test on the process of changing waste used oil, it was found that there were many weaknesses like the high viscosity value and the high content of water in the resultant product. But for other physical properties had fulfilled the standard of the fuel.Keywords: Temperature, used oil, pyrolysis, liquid fuel.